A 1D High Performance Thin Layer Chromatography Method Validated to Quantify Phospholipids Including Cardiolipin and Monolysocardiolipin from Biological Samples. Issue 2 (30th October 2019) - Pinault, Michelle; Guimaraes, Cyrille; Dumas, Jean‐François; Servais, Stéphane; Chevalier, Stephan; Besson, Pierre; Goupille, Caroline
Abstract: The aim of this study is to identify high performance thin layer chromatography (HPTLC) conditions allowing the separation and quantification of mammalian cellular phospholipids (PLs) (sphingomyelin, phosphatidylcholine, phosphatidylserine, phosphatidylinositol, phosphatidylethanolamine, and especially phosphatidic acid, cardiolipin, and monolysocardiolipin, these latter two being specifically located in mitochondria membranes). In order to make this method faster and easier, a 1D HPTLC method is chosen, testing several eluents as well as several staining methods. A pre‐conditioning of HPTLC plates with boric acid and a copper staining reagent followed by carbonization are selected for the quality of PL separation and homogeneity of staining. The selected conditions are discussed and the method validation is performed according to the International Conference on Harmonization guidelines. Linearity is effective between 1 and 8 µg and limit of quantification is between 0.5 and 2.3 µg depending on PL classes. Precision measurements show coefficients of variation <6%, and when amounts are close to the detection limit, <12%. Lipid extracts of tumor cell lines or isolated mitochondria are used to assess PL profiles. This shows that the HPTLC method can be used routinely to follow level variations of PLs. Practical Applications : The changes in PL composition play a crucial role in tumor processes and regulate cellular functions modulating cellular signaling or mitochondrial metabolism. The simple and cost‐effective 1D HPTLC method that is developed is applied to lipid extracts of whole tumor cells or hepatocyte‐isolated mitochondria. It is sensitive as well as precise to detect variations of phosphatidic acid or cardiolipin levels linked to physio‐pathological conditions. It can also be used to investigate the composition changes of other membrane PLs. Moreover, with a simultaneous analysis of 14 samples/standards on the same plate (six plates per day), this method is adapted for large series of samples. Abstract : Phospholipid analysis by HPTLC: a time‐ and solvent‐saving method to analyze cellular PL composition. After validation, the method is successfully applied to quantify PLs in lipid extracts from whole mammary tumor cells or hepatocytes‐isolated mitochondria. It can therefore be used to monitor PLs modifications potentially accompanying physio‐pathological changes. Cells and mitochondria pictures are modified from Servier Medical Art.